2018
DOI: 10.1101/313064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hunter-gatherers maintain assortativity in cooperation despite high-levels of residential change and mixing

Abstract: SUMMARYWidespread cooperation is a defining feature of human societies from hunter-gatherer bands to nation states. But explaining its evolution remains a challenge. While positive assortment – of cooperators with cooperators – is recognized as a basic requirement for the evolution of cooperation, the mechanisms governing assortment are debated. Moreover, the social structure of modern hunter-gatherers, characterized by high mobility, residential mixing and low genetic relatedness, undermine assortment and add… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 53 publications
(97 reference statements)
2
38
0
Order By: Relevance
“…If camps with more cooperative norms persist longer, as has been shown in some hunter-gatherer populations [20], then these learning dynamics could sustain substantial levels of cooperation within the population as a whole. Consistent with this, Apicella and colleagues [4] show that, while their prior behavior is not instructive, the single best predictor of how much a…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…If camps with more cooperative norms persist longer, as has been shown in some hunter-gatherer populations [20], then these learning dynamics could sustain substantial levels of cooperation within the population as a whole. Consistent with this, Apicella and colleagues [4] show that, while their prior behavior is not instructive, the single best predictor of how much a…”
mentioning
confidence: 71%
“…Many plants experience natural fluctuations in the saline and osmotic environments around roots and it is not surprising that most have evolved a range of tolerance mechanisms of varying effectiveness. The mechanisms underlying responses to increased salinity and tolerance of moderate salinity have been well studied in model plant systems, such as Arabidopsis and certain crop plants [3,4]. Such studies have shown key roles of a number of transporters for Na + , Cl À and K + in facilitating Na + exclusion from the cytoplasm.…”
Section: Current Biologymentioning
confidence: 99%
See 3 more Smart Citations